INCREASING LEARNING OUTCOMES AMONG PRIMARY SCHOOL STUDENTS BY USING CLASSROOM MANAGEMENT - K. A. Rahman; Mohamad Muspawi; Muazza Muazza; Panji Firman Kurniawan (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2019)
Abstract:This study aimed to determine the implementation of classroom management, and to find out the supporting and inhibiting factors in improving the students’ learning outcomes. This research used qualitative method which focused on interviewing the principal and teachers. The data were analyzed through classifying the data, coding and theme creation, then presenting the results. The finding of this study indicated that classroom management had impact on students’ learning outcomes. There were also some supporting factors, such as coordination and motivation from the school and parents who had big part in encouraging the improvement of the students’ learning outcomes. However, there were inhibiting factors, such as learning environment which was not conducive.Abstrak:Penelitian ini bertujuan untuk menentukan implementasi manajemen kelas, serta faktor pendukung dan penghambat dalam meningkatkan hasil belajar siswa. Penelitian ini menggunakan metode kualitatif yang berfokus pada wawancara kepala sekolah dan guru. Data dianalisis melalui pengklasifikasian data, pengkodean dan pembuatan tema, kemudian menyajikan hasilnya. Temuan dari penelitian ini menunjukkan bahwa manajemen kelas berdampak pada hasil belajar siswa. Terdapat juga beberapa faktor pendukung, seperti koordinasi dan motivasi dari sekolah dan orang tua yang berperan besar dalam mendorong peningkatan hasil belajar siswa. Namun, ada beberapa faktor penghambat, seperti lingkungan belajar yang tidak kondusif.